ECOFOAM: EDUCATION AND TRAINING IN DISHWASHING SOAP MAKING - Wahyu Nur Azizah Wahyu (International Islamic Schools Alliance, 2025)
Social Community Service (SCS) group 208 of Universitas Sebelas Maret carried out the Ecofoam activity: Education and Training on Dish Soap Making in Sendangagung Village, Plaosan District, Magetan Regency. This activity aims to increase public knowledge and skills in producing environmentally friendly dish soap as an effort to reduce dependence on commercial cleaning products. The implementation methods include socialization, demonstration, and direct practice involving PKK women as the main participants. The results of the activity showed a high level of participation, where most participants were able to produce good quality dish soap even though they had no previous experience. This activity has a positive impact on two main aspects, namely increasing environmental awareness regarding the dangers of using synthetic chemicals and opening up household business opportunities based on natural soap products that have the potential to increase family income. Thus, the Ecofoam program contributes to community empowerment, strengthening economic independence, and increasing environmental awareness in Sendangagung Village.